2010
DOI: 10.1002/mabi.201000332
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Effects Achieved by Co‐Delivery of TRAIL and Paclitaxel Using Cationic Polymeric Micelles

Abstract: Cationic micellar nanoparticles self-assembled from a biodegradable amphiphilic copolymer have been used to deliver human TRAIL and paclitaxel simultaneously. Polyplexes formed between paclitaxel-loaded nanoparticles and TRAIL are stable with a size of ≈180 nm and a zeta potential at ≈75 mV. Anticancer effects and apoptotic pathway mechanisms of this drug-and-protein co-delivery system are investigated in various human breast cancer cell lines with different TRAIL sensitivity. The co-delivery nanoparticulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The maximum tolerated dose of PGG-PTX was found to be 350 mg PTX/kg, which is 2.2-fold higher than the maximum tolerated dose of 160 mg PTX/kg reported for the PGA-PTX [88]. In a different study, cationic micellar nanoparticles self-assembled from a biodegradable amphiphilic copolymer were used to deliver human TRAIL (Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand) and Paclitaxel simultaneously [89]. Polyplexes formed between Paclitaxel-loaded nanoparticles and TRAIL were observed to be stable, with a size of about 180 nm and a zeta potential at about 75 mV.…”
Section: Taxolmentioning
confidence: 99%
“…The maximum tolerated dose of PGG-PTX was found to be 350 mg PTX/kg, which is 2.2-fold higher than the maximum tolerated dose of 160 mg PTX/kg reported for the PGA-PTX [88]. In a different study, cationic micellar nanoparticles self-assembled from a biodegradable amphiphilic copolymer were used to deliver human TRAIL (Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand) and Paclitaxel simultaneously [89]. Polyplexes formed between Paclitaxel-loaded nanoparticles and TRAIL were observed to be stable, with a size of about 180 nm and a zeta potential at about 75 mV.…”
Section: Taxolmentioning
confidence: 99%
“…Lee et al showed that micelles fabricated from an amphiphilic cholesterol-bearing copolymer, ie, poly[N-methyldietheneamine sebacate-co(cholesteryl oxocarbonylamido ethyl) methyl bis (ethylene) ammonium bromide sebacate], achieved a high paclitaxel loading of about 14% with an encapsulation efficiency of about 92% using a simple self-assembly process without homogenization or sonication. 21 Cabazitaxel (previously also known as taxoid, XRP6258, TXD258, or RPR 116258A) is a novel antineoplastic agent belonging to the taxane class. Due to its poor affinity for P-glycoprotein, cabazitaxel has demonstrated antitumor activity not only against docetaxel-sensitive tumor models but also against docetaxel-insensitive tumor models.…”
mentioning
confidence: 99%
“…126 In a very recent study, cationic micellar nanoparticles self-assembled from a biodegradable amphiphilic copolymer were used to deliver human TRAIL and paclitaxel simultaneously. 127 Polyplexes formed between paclitaxel-loaded nanoparticles and TRAIL was observed to be stable, with a size of approximately 180 nm and a zeta potential at about 75 mV. Anticancer effects and apoptotic pathway mechanisms of this drug-and-protein codelivery system were investigated in various human breast cancer cell lines with different TRAIL sensitivity.…”
Section: Paclitaxelmentioning
confidence: 99%